Estimation of Carbon Stock in the Sylhet Basin Soils of Bangladesh - Uddin, MJ; Rahman, Arafat; Ali, AHM Zulfiquar; Rahman, Md Khalilur (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Wetland basin soils are the major store houses of organic carbon where there is a scope to use this carbon in mitigating the climate change. A study was conducted in these basin soils at 100 cm depth regarding their carbon stock. The study showed that total soil organic carbon (SOC) stock in the Sylhet basin soils of Bangladesh is 0.094 Pg where the SOC stock was 0.044 Pg in medium low land sites and it was about 0.050 Pg in lowland sites. There was no previous study on SOC stock in the Sylhet basin soils of Bangladesh. These may act as benchmark SOC stock datasets for the future agricultural planning. The soil organic carbon stock is higher in the lowland than medium lowland sites. The contents of SOC are low is compared to its threshold levels. Moreover, it is apprehended that basin soils may lose their carbon due to the decrease of inundation level by climate change, and other eco-environmental changes. So, it is very much urgent to take steps in preserving the organic carbon of lowland basin soils. J. Asiat. Soc. Bangladesh, Sci. 46(1): 49-60, June 2020